2014
DOI: 10.1371/journal.pone.0096832
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Method to Examine Protein-Nucleotide Interactions Identifies Targets of the Bacterial Transcriptional Regulatory Protein Fur

Abstract: The Ferric uptake regulatory protein (Fur) is a transcriptional regulatory protein that functions to control gene transcription in response to iron in a number of pathogenic bacteria. In this study, we applied a label-free, quantitative and high-throughput analysis method, Interferometric Reflectance Imaging Sensor (IRIS), to rapidly characterize Fur-DNA interactions in vitro with predicted Fur binding sequences in the genome of Neisseria gonorrhoeae, the causative agent of the sexually transmitted disease gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…These studies demonstrate that 70% of the predicted Fur boxes in promoter regions of iron-induced genes bound to Fur, in vitro , with a range of affinities as observed using this microarray screening technology. Combining binding data with mRNA expression levels in a gonococcal Fur mutant strain allowed for the identification of five new gonococcal genes under Fur-mediated direct regulation [ 20 ].…”
Section: Applications and Resultsmentioning
confidence: 99%
“…These studies demonstrate that 70% of the predicted Fur boxes in promoter regions of iron-induced genes bound to Fur, in vitro , with a range of affinities as observed using this microarray screening technology. Combining binding data with mRNA expression levels in a gonococcal Fur mutant strain allowed for the identification of five new gonococcal genes under Fur-mediated direct regulation [ 20 ].…”
Section: Applications and Resultsmentioning
confidence: 99%
“…[21][22][23][24][25] The amount of protein binding to surfaceimmobilized DNA is measured by white light reflectance spectroscopy (WLRS), which quantifies molecular surface densities via measuring surface-immobilized biomolecule layer thicknesses. 22,[26][27][28][29][30] By implementing a dual-spectral imaging configuration, we can perform the two independent interferometric measurements simultaneously using two separate spectral ranges for multiple DNA spots simultaneously (Fig. 1, see Experimental, optical setup).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, new microarray formats have been developed that directly measure target concentrations via changes in the optical properties of the sensor itself as a function of bound target. 1013 These label-free technologies can have high sensitivities, but often have more stringent requirements for regular and uniform deposition of capture molecules, as compared to fluorescent methods, which are insensitive to localized variability in the z direction. 14,15 Regardless of the type of assay, the surface functionalization and immobilization procedures must be carefully considered since these directly affect the probe density and orientation on the substrate, which in turn affects the amount of target bound.…”
mentioning
confidence: 99%
“…In this format, a wide variety of proteins, nucleic acids, or small molecules can be targeted by immobilizing different probe biomolecules, including proteins, peptides, antibodies, sugars, enzymes, or aptamers, with the requisite specificities. ,− Binding of the target is most often detected by measuring fluorescence intensity changes from labeled tags either on the target itself (direct mode) or on a 2° antibody (sandwich). Alternatively, new microarray formats have been developed that directly measure target concentrations via changes in the optical properties of the sensor itself as a function of bound target. These label-free technologies can have high sensitivities but often have more stringent requirements for regular and uniform deposition of capture molecules, as compared to fluorescent methods, which are insensitive to localized variability in the z direction. , Regardless of the type of assay, the surface functionalization and immobilization procedures must be carefully considered since these directly affect the probe density and orientation on the substrate, which in turn affects the amount of target bound. It has been observed that directly immobilizing biomolecules onto planar surfaces results in significant unfolding/denaturing of proteins, translating to a loss of ligand binding activity, adversely affecting the assay’s ultimate performance. Thus, increasing the density, uniformity, and integrity of probe molecules on planar surfaces is an important subject of research.…”
mentioning
confidence: 99%